2012
DOI: 10.1523/jneurosci.4930-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

P2X4Receptors Influence Inflammasome Activation after Spinal Cord Injury

Abstract: P2X 4 and P2X 7 are the predominant purinergic P2X receptor subtypes expressed on immune and neural cells. These receptor subtypes traffic between intracellular compartments and the plasma membrane and form protein interactions with each other to regulate ATPdependent signaling. Our recent studies have shown that P2X 7 receptors in neurons and astrocytes activate NLRP1 inflammasomes, but whether P2X 4 receptors regulate inflammasome signaling is essentially unknown. Here, we demonstrate that P2X 4 receptors ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
141
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(150 citation statements)
references
References 46 publications
5
141
0
Order By: Relevance
“…P2X4R activation has been suggested to mediate IL-1β released in microglia [35]. P2X4 knock-out (KO) mice showed impaired inflammasome signaling in the cord, resulting in decreased levels of IL-1β [36]. The mechanism may be that P2X4R activation induces increased intracellular calcium concentrations, calcium as a second messenger activation of mitogen-activated protein kinases, and release of proinflammatory cytokines [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…P2X4R activation has been suggested to mediate IL-1β released in microglia [35]. P2X4 knock-out (KO) mice showed impaired inflammasome signaling in the cord, resulting in decreased levels of IL-1β [36]. The mechanism may be that P2X4R activation induces increased intracellular calcium concentrations, calcium as a second messenger activation of mitogen-activated protein kinases, and release of proinflammatory cytokines [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that P2X7 receptor overexpression is both necessary and sufficient to drive these processes (Monif et al, 2009). Other studies (de Rivero Vaccari et al, 2012), however, revealed the importance of IL-1b release from neurons, while Silverman et al (Silverman et al, 2009) report that in neurons, high extracellular K þ can activate the inflammasome via Panx1-dependent efflux. These latter data indicate that neurons may be the first site of IL-1b release following an insult (Fig.…”
Section: The Role Of P2x Receptors In Neuroinflammationmentioning
confidence: 98%
“…Interestingly, this process appears to be Panx1-independent (Bernier, 2012). A recent study showed that P2X4 knockout mice displayed impaired inflammasome activation resulting in a decrease in extracellular IL-1b and reduced infiltration of neutrophils and monocyte-derived M1 macrophages following spinal cord injury (de Rivero Vaccari et al, 2012). Further, Compan et al (2012) report that receptors made up of P2X2 and P2X5 subunits, which are expressed in specific neuronal populations, also show an ability to form a P2X7 receptor-like dilated pore, suggesting that these receptors may also function as gatekeepers of the inflammasome.…”
Section: The Role Of P2x Receptors In Neuroinflammationmentioning
confidence: 99%
“…19 In addition, deletion of P2X4 in mice results in decreased innate immune responses after SCI compared with wild-type animals. 20 This decreased inflammatory response involves a significant reduction in inflammasome activation in neurons as determined by decreased cleavage of caspase-1 and production of IL-1b, as well as decreased infiltration of immune cells into the injury site acutely after SCI. Pannexin-1, P2X4, and P2X7 have not been linked to NLRP1 inflammasomes in hematopoietic cells, yet pannexin-1 and P2X7 may influence NLRP3 inflammasome activity.…”
Section: The Nlrp1 Inflammasomementioning
confidence: 99%
“…The effects of knocking out NLRP1 or ASC in mice after SCI remains to be explored, yet P2X4 knockout mice, show decreased inflammasome activation after SCI, consistent with improved histopathological and functional outcomes. 20 Importantly, P2X4 was present in neurons of the spinal cord. Therefore, these data corroborate the therapeutic potential of targeting the inflammasome in neurons to improve outcomes after SCI.…”
Section: The Nlrp1 Inflammasomementioning
confidence: 99%